Poezja ogrodów Marii Pawlikowskiej-Jasnorzewskiej - Smolińska, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
The aim of the work is to trace personal various poetic images of Maria Pawlikowska- Jasnorzewska connected with the motive of the garden on the example of selected poems from early to the wartime ones. The article is an attempt to read the lyric sensitivity of the writer in the description of the world of garden plants, to discover her painting, philosophical and religious inclinations. Individual fragments of the work are devoted to the following jjnages: the garden of love and pleasure, the modernistic fantastic garden, the exotic garden, Tatra garden as well as the imagined or reminded places that are the mirror of the poet’s soul. The interpretation of the poems is accompanied by the study on the evolution of the style, imagination as well as the poet’s religious thought. The latter part of the work includes conviction of the appearance of many artistic inspirations in the literary output of M. Pawlikowska-Jasnorzewska comprising the romantic and modernistic literature together with influences of symbolism, impressionism, naturalism as well as Hinduism and Japanese painting which apart from Biblical tradition compose a peculiar poetic collage.